Rituximab for Remission Induction and Maintenance in Refractory Systemic Lupus Erythematosus (2014)
Systemic lupus erythematosus (SLE) is a chronic inflammatory autoimmune disease with high morbidity if untreated. Sometimes, despite aggressive treatments, the disease remains active with cumulative organic damage. We conducted a retrospective and descriptive observational study of patients with SLE refractory to conventional treatment who were treated with rituximab (RTX) as remission induction therapy and maintenance. There was a significant reduction in the conventional immunosuppressive drug dose and the number of relapses of disease. RTX appeared to be effective and safe for the induction and maintenance of remission in patient with SLE refractory to conventional treatment. © 2014 Fabio Bonilla-Abadía et al.